(untitled) (Al-Qamar, 2022)
The cult of ḥadīth commentators used to remain curious in the style of ḥadīth for seeking precision. While interpreting the ḥadīth, the interrelated and intra-related discourses used to be mentioned often briefly and sometimes concisely depending on the circumstance and situation. Consequently, the styles of commenting ḥadīth mutually differ. During the explanatory notes in his book, it seems that Maulānā Sahāranpurī renders the arguments about his perception and cult in detail. At the time of presenting his opponents’ arguments, excessive detail is not his primary concern and objective. So, same method has not been served at each turn, rather, different methods relating to jurisprudential schools of thought has been adopted. According to the writer, the purpose of Sahāranpurī is to make the reader realized about whatsoever issues and solutions derived by a jurist from the particular ḥadīth, the scholastical arguments and opponents’ argumentative answers. The foremost significant matter according to sufficient literary discourse, has been mentioned prior where it seemed appropriate. That is the reason, the jurisprudential precedent at some places, has been given even before the argument. Although the jurists mention such arguments at the end, as is the style of Imam Ṭaḥāwī. At some places, arguments has been presented by him prior to the conceptual discourse. Anyhow, beyond all of the above styles of Sahāranpurī, any sign of prejudice and aggression is not seemed in his pervasive and seminal work, as that seems in the commentaries of some commentators.